Transition-Metal-Catalyzed Intermolecular C–H Carbonylation toward Amides - Li, Yan-Lin; Gu, Zheng-Yang; Xia, Ji-Bao (Synlett, 2021)
The amide linkage is one of the most important structural moieties in both chemistry and biology. Here, we briefly discuss recent advances in catalytic intermolecular C–H carbonylation reactions for the synthesis of amides, with particular attention to our intermolecular C–H amidation of arenes with carbon monoxide and organic azides to produce amides.1 Introduction2 Representative Methods for Amide Synthesis3 C–H Aminocarbonylation with Carbon Monoxide and Amines4 C–H Amidation to Amides with Carbon Monoxide and Azides5 Summary and Outlook
Keywords: C–H functionalization; amidation; carbon monoxide; azides; isocyanates; amide